IMPLEMENTASI BIMBINGAN KONSELING UNTUK MENANGANI STRES AKADEMIK BERBASIS KEARIFAN LOKAL NIAS PADA MAHASISWA - Kaminudin Telaumbanua (Universitas Nias Raya, 2024)
Academic stress is one of the main challenges faced by university students, which can affect their mental and emotional well-being as well as their academic performance. To address this issue, this community service program aims to implement Nias-based counseling guidance as an innovative approach to help students manage academic stress. Through this approach, students are provided with an understanding of the values of Nias culture, which emphasize musyawarah (deliberation), gotong royong (mutual cooperation), and faluaya (unity in togetherness) as the foundation for solving problems collectively. The counseling program includes both individual and group sessions designed to provide coping skills, relaxation techniques, and social support necessary for managing academic stress. The results of the program show that students who participated in this counseling experienced a significant reduction in academic stress and felt more connected to their own culture. Additionally, they improved skills in time management, reduced anxiety, and strengthened social bonds and solidarity among their peers. This program successfully demonstrated that a Nias-based local wisdom approach can be an effective strategy for helping students overcome academic stress in a more holistic way that is relevant to their cultural context.